Analisis Perilaku Konsumen Nano Store di Kota Bandung Pada Masa Pandemi Covid-19 - Mathew, Alan (Asosiasi Ahli Administrasi Indonesia, 2021)
The Covid-19 pandemic affects many aspects of life, one of which is the economic sector. Almost all businesses in the world have been affected by the Covid-19 pandemic. The impact was felt on the smallest businesses, namely the nano store. One of the things that businesses have been affected by this pandemic is the behavior of consumers. The purpose of this study is to determine the consumer behavior of nano stores in the city of Bandung during the Covid-19 pandemic. The method used in this study is a qualitative descriptive analysis method with data collection techniques using a closed questionnaire by determining the number of samples using an internal approach. The number of samples in this study were 106 respondents. The results of this study indicate that the consumer behavior of Bandung's-Indonesia nano stores during the Covid-19 pandemic was quite influenced by the Covid-19 pandemic.